A new species of Streothrips (Thysanoptera:Aeolothripidae) from Malaysia, with description of male and key to species - Ng, Y. F.; Eow, L. X. (Zootaxa, 2012)
Streothrips moundi sp. n. is described from Malaysia based on both sexes, and a key is provided to the three known speciesof this Asian genus. This is the first record of any Aeolothripidae from Malaysia, and the first description of a male Streo-thrips. The male has a pair of tubercles on the posterolateral angles of the seventh abdominal segment, unlike any other recorded male in the Aeolothripidae.